2002
DOI: 10.1295/polymj.34.325
|View full text |Cite
|
Sign up to set email alerts
|

Complete Spectral Assignment of Poly(N-Vinylcarbazole-co-Methyl Acrylate)s by NMR Spectroscopy

Abstract: ABSTRACT:The copolymers of N-vinylcarbazole/methyl acrylate (V/M) of different compositions were prepared by solution polymerisation using 2,2'-Azobisisobutyronitrile (AIBN) as an initiator and their composition was determined from quantitative 13 C{ 1 H} NMR spectroscopy. Reactivity ratios for the comonomers were calculated using the Kelen-Tudos (KT) and non-linear error in variable methods (EVM). The complete spectral assignment of the overlapping 1 H and 13 C{ 1 H} spectra of the copolymers were done with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2003
2003
2010
2010

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 12 publications
0
26
0
Order By: Relevance
“…The composition of terpolymers obtained from quantitative 13 C{ 1 H} NMR spectra were found to be in good agreement with those calculated from Alfrey-Goldfinger's equation [28]. The reactivity ratio of the comonomers calculated from Kelen-Tudos (KT) method are found as: r MA = 6.74 ± 1.03, r AM = 0.04 ± 0.01 for M/A copolymers [29], r AC = 0.26 ± 0.09, r CA = 5.86 ± 1.54 for A/C copolymers [22] and r MC = 0.65 ± 0.13, r CM = 0.07 ± 0.03 for M/C copolymers [21] while the reactivity ratio values observed from Error in Variable method (EVM) are: r MA = 6.72, r AM = 0.04 for M/A copolymers [29], r AC = 0.24, r CA = 5.41 for A/C copolymers [22] and r MC = 0.73, r CM = 0.08 for M/C copolymers [21].…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…The composition of terpolymers obtained from quantitative 13 C{ 1 H} NMR spectra were found to be in good agreement with those calculated from Alfrey-Goldfinger's equation [28]. The reactivity ratio of the comonomers calculated from Kelen-Tudos (KT) method are found as: r MA = 6.74 ± 1.03, r AM = 0.04 ± 0.01 for M/A copolymers [29], r AC = 0.26 ± 0.09, r CA = 5.86 ± 1.54 for A/C copolymers [22] and r MC = 0.65 ± 0.13, r CM = 0.07 ± 0.03 for M/C copolymers [21] while the reactivity ratio values observed from Error in Variable method (EVM) are: r MA = 6.72, r AM = 0.04 for M/A copolymers [29], r AC = 0.24, r CA = 5.41 for A/C copolymers [22] and r MC = 0.73, r CM = 0.08 for M/C copolymers [21].…”
Section: Resultsmentioning
confidence: 88%
“…1a. Various resonance signals were assigned by comparing 13 C{ 1 H} NMR spectra of terpolymers with N-vinyl carbazole/methyl acrylate [21], N-vinyl carbazole/vinyl acetate [22] and vinyl acetate/methyl acrylate [29] copolymers and their respective homopolymers [17,18,30,31]. Complex and overlapped methoxy, methine, methylene and carbonyl carbons were further resolved with the help of DEPT-135 NMR spectrum (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that copolymerization has a great influence on thermal properties of polymer [25,26].…”
Section: Introductionmentioning
confidence: 99%